An overview on the application of supercritical carbon dioxide for the processing of pharmaceuticals - Milovanović, Stoja; Lukić, Ivana (Archives of Pharmacy, 2022)
Supercritical carbon dioxide (scCO2) application in the pharmaceutical industry is still undeveloped regardless of significant research interests in this processing medium shown in the last decades. ScCO2 technologies can improve drug solubility, bioavailability, and therapeutic effect. These technologies can lead to the development of new formulations that will contribute to a decrease in drug dose, medication frequency, and increase patients’ well-being. Considering the significant decrease in the price of high-pressure equipment and society's growing need for cleaner production and safer products, it is expected that symbiosis between supercritical fluid and pharmaceutical technologies will happen soon. Therefore, this review was focused on the latest contributions of scCO2 technologies to the pharmaceutical field. The main aim was to bring these technologies closer to pharmaceutical specialists. For this purpose, the most commonly used technologies were explained and discussed: the preparation of solid dispersions, polymer impregnation with drugs, and drug micro/nanoparticle production using scCO2.
Keywords: supercritical CO2; solid dispersion; supercritical impregnation; particle generation